Rediscovering Fritz Redl - Jack Phelan (Scottish Journal of Residential Child Care, 2013)
If there was a Hall of Fame for Child and Youth Care practitioners, the first person I would nominate is Fritz Redl. I had been in the field for two years when I first read Children Who Hate, and I was amazed at the description of youth that so accurately mirrored my own experience. Fritz and fellow author David Wineman explained CYC ideas better than anyone I had ever met. The complexity of our work and the use of life spaces to create healing came alive in the descriptions of his work at Pioneer House, a group home for boys.